The dynamics of online sexual grooming: From comfort to insecurity in victims' experiences - Vrisaba, Nanda Audia; Faidah, Mutimmatul; Purba, Iman Pasu Marganda Hadiarto (Empathy : Jurnal Fakultas Psikologi, 2024)
The prevalence of sexual violence has been rising, particularly with the increasing reports of online sexual abuse. This study aims to examine the experiences of victims subjected to online sexual grooming, a form of sexual violence occurring in digital spaces. The research focuses on the manipulative tactics employed by perpetrators to exploit their victims. Using a qualitative approach and a phenomenological study design, the research involved two participants who had been victims of online sexual grooming by unknown perpetrators, with no prior face-to-face contact. Data were collected through interviews, and analysis followed the stages of data reduction, data presentation, and drawing conclusions. Findings reveal that prior to the grooming process, participants encountered the perpetrators via social media and engaged in frequent conversations. Throughout the grooming process, perpetrators employed various manipulative techniques such as conversational manipulation, sustained contact, secrecy, sexualization, compliments, erratic moods, and other grooming behaviors. The emotional impact of online sexual grooming on the victims included both positive and negative feelings, with the latter predominating during the grooming experience.